Determining different plant leaves fractal dimensions: a new approach to taxonomical study of plants - Bayirli, Mehmet; Selvi, Selami; Cakilcioglu, Ugur (Bangladesh Journal of Botany, 2015)
Fractal dimensions of leaves from Cercis canadensis L., Robinia pseudoacacia L., Amelanchier arborea (F.Michx.) Fernald, Prunus persica (L.) Batsch, Quercus alba L., Carpinus caroliniana Walter, Ficus carica L., Morus rubra L., Platanus orientalis L., and Ulmus rubra Muhl. were calculated. The values were then confirmed and compared by those obtained from box-counting method and the exponent values of densitydensity correlation function (first time in the literature). It is now proposed for the first time that there is a relationship between a fractal dimension of the leaf and a surface density of the image and was concluded that together with other measures, the fractal dimensions with surface density function could be used as a new approach to taxonomical study of plants. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21593 Bangladesh J. Bot. 43(3): 267-275, 2014 (December)